Cardiac arrest complicating ocular pilocarpine administration. Issue 1 (27th April 2015) - Heath, Charlotte; Ball, David
Summary: Topically applied eye drops may be absorbed systemically and this occasionally results in complications. We report a cardiac arrest following postoperative pilocarpine administration to the eye.